Uterine artery embolization, not cesarean section, as an option for termination of pregnancy in placenta previa - Lingling Huang; Reenu Awale; Hui Tang; ZhiShan Zeng; FuRong Li; Yue Chen (Elsevier, 2015)
Objective: To summarize our experiences in the treatment of labor induction in placenta previa using uterine artery embolization. Case report: We retrospectively analyzed the clinical data of seven patients with placenta previa who underwent antepartum uterine artery embolization before vaginal delivery. After antepartum embolization, five patients with placenta previa had successful vaginal deliveries and two cases of placenta previa with accreta underwent emergency hysterectomy. Some complications were reported in this experience. The follow-up study showed that most patients resumed their normal menstruation and some of them were able to conceive. Conclusion: For the management of placenta previa, uterine artery embolization is a minimally invasive technique that helps to avoid cesarean section. The impact on menstruation and fertility is yet to be seen.